Comparison of Dexmedetomidine with Tramadol for Treatment of Shivering Post Spinal Anaesthesia - Ranjha, Chaudhry Raheel; Saeed, Muhammad; Mehmood, Basit; Hayat, Umer; Sana Abbas; Terrence, Arona (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the efficacy of Dexmedetomidine with Tramadol for shivering post-spinal anaesthesia. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Anaesthesia, Combined Military Hospital, Rawalpindi Pakistan, from Jul to Dec 2020. Methodology: A total of 158 patients who underwent gynaecological, orthopaedic and general surgical procedures under spinal anaesthesia using 0.5% hyperbaric Bupivacaine 12-15 mg were included in the study. Out of these 158 patients, 64% (102 patients) developed shivering after spinal anaesthesia. These 102 patients were divided into two equal groups, i.e., Group-D (n=51), who received 0.5 μg/kg Dexmedetomidine and Group-T (n=51), who received 0.5 mg/kg tramadol. The response in the next 15 mins was evaluated objectively as “effective” or “non-effective” by the treating Anesthesiologist. Results: Dexmedetomidine and Tramadol were effective in treating shivering following spinal anaesthesia. Our study showed that Dexmedetomidine was more effective than Tramadol in treating shivering, with an effectiveness of 88.2 % shivering relief in Group-D and an effectiveness of 51 % shivering relief in Group-T. The effectiveness was significant in both groups, with statistical significance in Group-D compared to Group-T (p<0.05). Conclusion: Shivering relief was more responsive in patients who received Dexmedetomidine than Tramadol after spinal anaesthesia.